Effect of alcohol coadministration on the pharmacodynamics, pharmacokinetics, and safety of lemborexant: A randomized, placebo-controlled crossover study. (June 2022) - Landry, Ishani; Hall, Nancy; Aluri, Jagadeesh; Filippov, Gleb; Setnik, Beatrice; Dayal, Satish; Reyderman, Larisa; Moline, Margaret
Background: Lemborexant is a dual orexin receptor antagonist approved to treat insomnia in adults in several countries including the USA, Canada, and Japan. Aims: This study was conducted to investigate effects of lemborexant and alcohol coadministration on postural stability, cognitive performance, and the pharmacokinetics, safety, and tolerability of lemborexant. Methods: This was a Phase 1, double-blind, placebo-controlled, four-period crossover study in 32 healthy adults. Individuals were randomized into one of four treatment sequences to receive single doses of placebo, lemborexant 10 mg (LEM10), alcohol (males, 0.7 g/kg; females, 0.6 g/kg), and LEM10 plus alcohol, each separated by a 14-day washout. Postural stability (body sway) was measured by ataxiameter and a cognitive performance assessment battery evaluated four domains of attention and memory. Results: Pharmacodynamic outcomes were analyzed for the 18 participants who completed all four treatments. Change from baseline in body sway showed no significant differences between lemborexant plus alcohol versus alcohol alone. Compared with alcohol alone, coadministration of lemborexant with alcohol showed additive negative effects on cognitive performance domains, corresponding approximately with peak plasma lemborexant concentrations (median = 1.5 h). Cognitive performance was also impaired with lemborexant alone at 0.5 and 2 h in this experimental paradigm with morning dosing. Alcohol increased plasma lemborexant exposure by 70% based on area under the curve to 72 h, and increased peak plasma lemborexant concentrations by 35%. The most commonly reported treatment–emergent adverse event was somnolence. Conclusion: Coadministration of lemborexant with alcohol showed additive negative effects on cognitive measures, but not on postural stability, compared with alcohol alone. Lemborexant exposure was increased with alcohol. Lemborexant alone or with alcohol was well tolerated. Patients are advised not to consume alcohol with lemborexant.